Key issues and drivers affecting coastal and marine resource decisions: Participatory management strategy evaluation to support adaptive management. (November 2015) - Dutra, Leo X.C.; Thébaud, Olivier; Boschetti, Fabio; Smith, Anthony D.M.; Dichmont, Catherine M.
Highlights: Improving resource information alone has limited effect on decision-making processes. A formal participatory MSE allows for more transparency in the management process. It supports strategy design, communication and shared understanding about management issues. Participatory methods can help modify individual attitudes and group interactions.